A novel germline BMPR1A variant (c.72_73delGA) in a Japanese family with hereditary mixed polyposis syndrome. (7th May 2020) - Miyahara, Yosuke; Ishida, Hideyuki; Kawabe, Koichi; Eto, Hiroyuki; Kasai, Toyotaka; Ito, Tetsuya; Kaneko, Kou; Arai, Motohiro; Kamae, Nao; Momose, Shuji; Eguchi, Hidetaka; Okazaki, Yasushi
Abstract: Hereditary mixed polyposis syndrome (HMPS) is a rare autosomal dominant disorder characterized by a mixture of typical and/or atypical juvenile polyps, adenomas and hyperplastic polyps, resulting in an increased risk of colorectal cancer. In HMPS, four different germline BMPR1A variants from five unrelated families have been reported. This study is the first to report HMPS within a Japanese family. The proband underwent repeated colonoscopic polypectomies over a 5-year period, since the age of 67. Histological examination of these resected polyps revealed adenomas, juvenile-like polyps and hyperplastic changes. Genetic testing was conducted to identify the causative genes for hereditary gastrointestinal cancer syndromes, including BMPR1A . We detected a germline variant, c.72_73delGA, in BMPR1A . The proband's elder brother, younger sister and nephew have also undergone repeated colonoscopic polypectomies at other clinics. His sister and nephew underwent genetic testing, and the same BMPR1A variant was identified. Abstract : We report a novel germline BMPR1A variant, c.72_73delGA, in a Japanese family with HMPS-2.